Paramyxoviral zoonoses associated with Chiroptera - V. V. Makarov; D. A. Lozovoy; A. A. Strizhakov (Ветеринария сегодня)
The paper describes natural historic aspects of emerging dangerous paromyxoviral infections associated with chiropteran reservoir species - Hedra, Nepah, Menangle viruses, their origin and spread.